Local government public servants performance and citizens participation in governance in Nigeria - Dibie, Robert (2003)
This paper examines the performance of public administrators at the local government level in Nigeria. It traces the development of local governments in Nigeria from 1945 to present times. It argues that the shift in the critical decision-making powers and functions of local government requires its public administrators to be better-trained professionals. However, without citizens' participation in governance, public servants' accountability will be low. The study addresses the following questions: How do public sector performance and development of actions by citizens affect accountability in the local governments? How much training do public administrators in Nigeria's local governments have in public management? What is the relationship between performance and citizenship participation in local governments' development process? The question of interests in this study is how public administration at the local government level can better serve Nigeria's communities and in so doing develop authentic relationship with citizen groups, and equitably enhance public trust, legitimacy, and performance of the public sector in the nation. - Reproduced.
Keywords: Public administration - Nigeria; Civil service - Nigeria; Local government - Nigeria; Local government